A intervenção do poder judiciário no acesso a medicamentos no Rio Grande do Norte: uma análise sob a ótica das políticas nacionais de medicamento e de assistência farmacêutica - Macêdo, Márcia Fernanda Silva (2013)
The present study aimed to evaluate the inclusion of the principles of the National Medicines Policy - PNM and the Pharmaceutical assistance - PNAF in the prosecution of lawsuits involving medicines. To fulfill this necessity , data collection was performed on the website by the Tribunal Rio Grande do Norte - TJ RN ( Rio Grande do Norte Court) , in 2012 . It was obtained 115 judgments, which were analyzed in order to generate Monitoring Indicators from lawsuits and conduct content analysis proposed by Bardin (2006). The results showed that : a) 100 % of the decisions were favorable to the author , b) 76 % of decisions were requests by the trade name of the drug , c) only one drug (eculizumabe) had not granted by ANVISA , d) 36 % of drugs were present in the list of standard medicines in SUS , 16 % of primary care block and 20 % of specialized component , e) 76 % of the decisions presented the request of at least 01 non-standard medicine. With regard to decentralization of PNM and PNAF we observed a commitment to this principle at judicial decisions, to see that municipalities and states are often forced to buy medicines of responsibility from another federal entity or other tertiary units as CACONs and UNACONS. The content analysis revealed that the argument from the judges used when you utter their decisions was that the right to health is recognized by Brazilian law as a fundamental right and should be guaranteed by the State for all its citizens. So, health is more than budgetary constraints of federal entities, which are severally liable for lawsuits , regardless the medication requested belongs or not to a particular block of a pharmaceutical assistance funding. Given these data, it is observed that there are gaps in the judgment when it comes to the insertion of the words and principles of PNM and PNAF, creating then the need for greater dialogue between the executive and judicial, so that they may consider relevant the effectiveness and application of such principles to minimize the negative consequences of the phenomenon of health judicialisation. Keywords: Judicialisation, Medicines, Public Policy, Pharmaceutical Care